PENGGUNAAN METODE COBIT FRAMEWORK 4.1 DALAM MENGAUDIT SISTEM INFORMASI AKADEMIK (SIAKAD) PADA IAIN RADEN INTAN LAMPUNG - RIFAI, RENDRA NASRUL; -, WASILAH (244-5567)
Academic activities in IAIN Raden Intan Lampung are growing (growing trend). The growth of students and lecturers needs (growing demand) demanding the information about Academic Information System (SIAKAD) for a faster and better information system, and the growth in the performance and capacity, system security and skill of the Human Resources, are expected to be in the highest performance, thus, academic information system audit is required in IAIN Raden Intan Lampung, particularly on the scale of performance and capacity measurement, system security, and Human Resources Training about SIAKAD. This research evaluated the application of SIAKAD by the management and user by applying COBIT Framework 4.1.  Key Performance Indicator (KPI) of DS3: to continually accumulate user trainings, evaluation and motivation are done weekly. Available working facilities have to be boosted up to 95% in order to keep the information system technology updated. Key Performance Indicators of DS5 are to provide skill training for the administrator or user in system security maintenance, and to design software SIAKAD that is not easy to be hi-jacked. Key Performance Indicator (KPI) of DS7 is to supervise the users training activity. Monthly evaluation/monitoring will ensure the performance of the activity will be boosted more by the management.The results of the research lead to a conclusion that the process of DS3, DS5, and DS7 in Monitoring and Evaluate given by Pusat Komputer IAIN Raden Intan Lampung is generally in the level of readiness of defined process. There is an indication that the institution knows the existing matters to be solved. Being processed using the standardized method in execution, has significantly defined the steps to be used in supporting the service. In general, the approach to the process management is well organized. Key Words : Framework Cobit 4.1, Audit SIAKAD, IAIN Raden Intan Lampung